LA VIOLENCE DANS LES RITES FUNERAIRES EN MILIEU RURAL BETE (Côte d’Ivoire) - Marcel, YORO Blé (European Scientific Journal, ESJ, 2012)
We try in this article, to describe the new forms of violence which have more and more runs in the funeral to bete. It arises from the analysis that these violences, generally perpetrated by the young people, are a form of desacralization of the funerary rites at the point where they mark in a certain manner not only the end of the respect due to deaths, but more especially put in danger the protection supposed of alive by the ancestors. But these violences seem to fall under the general sociopolitic context of the Côte d’Ivoire, characterized, since the death of first President Houphouet-Boigny on August 7, 1993, by “a brutalisation of the local sociopolitic life” (Vidal, C, 2003). Particularly the young townsmen like rural, weakened by the unemployment and poverty, and under the effect of alcohol and drug, tend more and more to exert violence like means of revalorization of oneself. Funerary spaces, formerly place of meditation are thus transformed into boxing ring, with large the dam of old, guards of the tradition, constrained to assist impotent, with the furia of a youth in loss.